Good luck or good management? Public sector audit in the Swan River Colony, 1828-1835 - Bunn, M.; Gilchrist, David (Wiley InterScience, 2011)
The role of the Auditor General in public sector audit is the primary instrument used to safeguard public finances and to assist in ensuring executive accountability and transparency in most contemporary Westminster-based democracies. The independence of the Auditor General from the executive government of the day is seen as a critical element for strengthening the effectiveness of the role, yet this separation is a relatively recent element. Analysis shows those responsible for 19th century public sector audit in the Swan River Colony of Western Australia operated in what would today be considered an unacceptable environment, with very little indepdence from the executive arm of government. It has been argued that colonial audit really operated an accounting function for the executive rather than as a public check on government expenditure. This is certainly the case for the Swan River Colony. Official government correspondence of the early Swan River Colony (among other sources) demonstrates there was a very thorough and highly structured system for managing government finances, one in which colonial auditors played a significant role despite a lack of independence. Several other Australian colonies suffered from mismanagement of government finances but there is nothing to show that the Swan River Colony experienced much more than clerical errors and minor administrative oversights. Was the lack of financial scandal just due to the good fortune that competent and ethical government administrators were selected for the Swan River colony? Or did the existing imperial and colonial financial administrative systems enable the colonial audit function to provide adequate checks and balances despite its limited role?